Associations Between Both Adaptive and Maladaptive Personality Constructs and Emotional Load and Content of Adult Dreams - Saeid Komasi; Amin Nazari; Behrooz Faridmarandi; Mozhgan Saeidi; Mostafa Bahremand; Taherh Shadman; Atefeh Mirani; Parisa Nazarpour; Zhaleh Kiani; Ali Zakiei (Indian Journal of Psychological Medicine)
Background: It seems that personality and dreams are relatively stable interwoven constructs that show many shared characteristics across cultures. The present study aimed to predict the emotional load and content of dreams using both original constructs and two extracted spectrum factors of adaptive and maladaptive personalities. Methods: The cross-sectional study data was collected from 704 Iranian adults using the brief version of the Personality Inventory for DSM-5 , the brief version of the Big Five Inventory, Schredl’s Dream Emotions Manual , and the Content Analysis of Dreams Manual . Pearson correlations, hierarchical regressions, exploratory factor analysis, and analysis of variance were used to analyse the data. Results: Factor analysis revealed two factors for the adaptive and maladaptive spectrums of personality. Adaptive and maladaptive constructs of personality are almost equally related to both the negative and positive loads of dreams, while the negative load of dreams is more strongly predicted by the maladaptive spectrum factor ( R 2 : 13% vs. 7%, ∆ R 2 : 8% vs. 2%). Negative load is characterized by low agreeableness and high negative affectivity, while positive load is characterized by high agreeableness and low detachment. Compared to most negative dream content such as distress, dreamers with happy content reported higher adaptive traits and lower maladaptive traits. Conclusions: The emotional load and content of dreams are significantly related to both specific constructs and spectrum factors of adaptive and maladaptive personalities. Psychologists can refer to personality profiles when analysing the emotional load and content of dreams of adults.